Relations Between Albanians and Croats Across the Centuries - Demiri, Naile (European Journal of Multidisciplinary Studies, 2016)
The Balkan Peninsula is part of South Eastern Europe, with a surface area of 550 square kilometers and a population of nearly 55 million inhabitants. This is a corner of the Earth with a very attractive geography. It is shaped like a triangle and goes deep into the Mediterranean Sea. This peninsula is bordered with the Adriatic Sea, Ionian Sea, Marmaris Sea, Aegean Sea, and the Black Sea, whereas on the other part with Central Europe. The Balkan Peninsula is, or serves, as a connecting bridge between Europe and Asia. The countries of the Balkan Peninsula are: a part of Turkey, Greece, Bulgaria, Romania, Serbia, Macedonia, Kosovo, Albania, Montenegro, Bosnia and Herzegovina and part of Croatia (up to Sava River).
Keywords: Relations, Albanians, Croats, Centuries